Governing the Face Veil: Quebec’s Bill 94 and the Transnational Politics of Women’s Identity - Sharify-Funk, Meena (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
During the last decade, a new pattern of cultural contestation has emerged in a range of “Western” contexts where there has been significant Muslim immigration. From Belgium and France to Quebec, Canada, anxieties concerning the integration and acculturation of Muslim minority communities have led to increased preoccupation with symbols associated with extremism and with practices deemed threatening to women’s rights. Muslim face veils such as the niqab and burqa now figure prominently in political debates, and are the subject of campaigns to reassert fundamental values by defining appropriate as well as inappropriate ways for women to construct and express their identities. Using Quebec’s Bill 94 as a case study that illustrates patterns also evident in other countries, this article explores the transnational politics of women’s identity behind current efforts to “govern” the face veil. Attention will be given to international precedents that have inspired proponents of legislation denying face-veil wearers essential government services (including public employment, educational opportunities, and health care), as well as to surprising anti-Bill 94 coalitions that have emerged within Quebec and in the larger Canadian context.